Verbal and nonverbal impression management tactics in behavior description and situational interviews - PEETERS, Helga (Institutional Knowledge at Singapore Management University, 2006)
This study investigated how structured interview formats, instructions to convey favorable impressions, and applicants' individual differences influenced the use and effectiveness of verbal and nonverbal impression management (IM). Results from 190 people who were screened for a training program demonstrated that interview format affected the kind of tactics used, which in turn positively influenced interviewer evaluations. Behavior description interviews triggered self-focused (and defensive) tactics, whereas situational interviews triggered other-focused tactics. Instructions to convey a desirable impression also enhanced the use of specific tactics (self-focused and other-focused verbal IM tactics) and moderated the effects of individual differences on IM use. IM instructions did not affect nonverbal IM tactics, indicating that nonverbal behavior might be less intentionally controllable in selection situations.